Prevalence of Trichomoniasis, Candidiasis, and HIV in Wanodyatama Social Rehabilitation Patients Surakarta - Setya, Adhi Kumoro; Trikusumaadi, Stefanus Khrismasagung; Wulandari, Septiana Wahyu; Anugrah, Tifani Sofiana; Fanani, Zulfi Maulita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The demands of modern life have significant impacts such as psychological and social stress on society. Conditions of economic pressure, increased promiscuity, drugs, harassment, and increasing marginalization due to disability make some individuals or groups vulnerable to health problems. This study aims to determine the prevalence of sexually transmitted infections (STIs) caused by Trichomonas vaginalis, Candida albicans, and Human Immunodeficiency Virus (HIV) in people caught in raids and receiving counseling at Wanodyatama social rehabilitation center Surakarta. This study used a descriptive survey study design with urine and blood samples from 40 female respondents. The presence of cases was evaluated using microscopic methods, isolation cultures and rapid immunochromatography tests. The results showed that Trichomonas vaginalis was detected microscopically in 1 sample (2.5%), Candida pseudohyphae in 2 samples (5%), and germ tube tests confirmed positive for Candida albicans in 2 isolates (12.5%). From the non-microscopic results, media culture showed 16 positive samples (40%) for Candida spp. and HIV rapid test showed positive results in 3 samples (7.5%). This study shows the prevalence of trichomoniasis is the lowest case (2.5%), while fungal infections, especially Candida spp., are higher (40%) and Candida albicans (12.5%), and cases of HIV infection in the population (7.5%).